2020
DOI: 10.1186/s12957-020-02024-1
|View full text |Cite
|
Sign up to set email alerts
|

A case of long-term survival after splenectomy for solitary splenic metastasis from gastric cancer

Abstract: Background Very rarely does a splenic solitary metastasis arise from a gastric carcinoma because splenic metastasis is usually seen in association with widespread visceral metastasis. Splenectomy is considered to be a curative treatment; however, long-term prognosis after splenectomy has scarcely been reported. We report a case of a metachronous and solitary metastasis to the spleen from gastric cancer in which the patient achieved 5-year recurrence-free survival after splenectomy. Case presentation An 84-ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In our patient with gastric cancer, two important issues were highlighted: splenic metastasis and SVTT. Because splenic metastasis of gastric cancer is usually associated with peritoneal dissemination or multiple visceral metastases, there are few reports of resection for solitary splenic metastasis [17]. Despite the anatomical proximity between the stomach and spleen, splenic metastasis of gastric cancer is rare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our patient with gastric cancer, two important issues were highlighted: splenic metastasis and SVTT. Because splenic metastasis of gastric cancer is usually associated with peritoneal dissemination or multiple visceral metastases, there are few reports of resection for solitary splenic metastasis [17]. Despite the anatomical proximity between the stomach and spleen, splenic metastasis of gastric cancer is rare.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 93 cases of solitary splenic metastasis reported that in 7.5% of cases, gastric cancer metastasis occurred [18]. Gastric cancer causes splenic metastasis through three pathways: (1) via the lymphatic route, (2) via the splenic vein, and (3) via the splenic artery [17]. The spleen has a poorly developed lymphatic system and few afferent lymphatic vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case 2, we suspected a metastatic tumor derived from adenocarcinoma of the ascending colon because of both the patient's medical history and the rapid enlargement of the tumor. Solitary splenic metastases are rare, but they can occur in some cases (13). It may have been better to perform a biopsy of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Metastases to the spleen from solid cancers are uncommon, with a prevalence of 2.3% to 7.1%. [3] Although splenic metastasis arises from gastric cancer, colorectal cancer, lung cancer, nasopharyngeal carcinoma, ovarian cancer, breast cancer, and other types of cancer, [4][5][6][7][8] isolated splenic metastasis from endometrial adenocarcinoma is extremely rare. To date, only 17 such cases have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%